The effect of concept-based instruction on EFL students’ learning perfect tenses - Nguyễn Tuấn Đạt (Trường Đại học Trà Vinh, 2024)
The main objective of the study is to investigate how Concept-based Instruction affects EFL students who are not English majors in their use of perfect tenses. The researcher then wants to know how EFL students feel about concept-based instruction for employing perfect tenses. The purpose is to inform students of their advancements in learning the perfect tenses.